(untitled) (Universal International Scientific Journal, 2026)
It is not enough to explain the social problems of the population solely through economic indicators (income, unemployment, inflation). In socio-philosophical analysis, any "problem" is a contradictory reality that manifests itself in the system of relations between human values, norms and criteria of justice, as well as institutions (state, market, family, education, neighborhood)